-5xy.(4x^2-3xy+2)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(=\left(4xy^2+2xy^2\right)+\left(3x^2y-3x^2y\right)=6xy^2\)
b: \(=xy\left(\dfrac{1}{5}+\dfrac{1}{3}\right)+xy^2\left(\dfrac{4}{3}-\dfrac{2}{5}\right)=\dfrac{8}{15}xy+\dfrac{14}{15}xy^2\)
d: \(=\dfrac{-4}{9}\cdot\dfrac{3}{2}\cdot xy^2\cdot xy^3=-\dfrac{2}{3}x^2y^5\)
\(\left(4x^2y-3xy-5\right)-\left(-3x^2y^2+5xy+\dfrac{1}{2}\right)\)
\(=4x^2y-3xy-5+3x^2y^2-5xy-\dfrac{1}{2}\)
\(=4x^2y-8xy+3x^2y^2-\dfrac{11}{2}\)
\(A=4x^2-5xy+3y^2\\\Rightarrow 2A=2\cdot(4x^2-5xy+3y^2)\\\Rightarrow2A=8x^2-10xy+6y^2\\B=3x^2+2xy+y^2\\\Rightarrow3B=3\cdot(3x^2+2xy+y^2)\\\Rightarrow3B=9x^2+6xy+3y^2\\C=-x^2+3xy+2y^2\)
Khi đó: $2A-3B-C$
$=(8x^2-10xy+6y^2)-(9x^2+6xy+3y^2)-(-x^2+3xy+2y^2)$
$=8x^2-10xy+6y^2-9x^2-6xy-3y^2+x^2-3xy-2y^2$
$=(8x^2-9x^2+x^2)+(-10xy-6xy-3xy)+(6y^2-3y^2-2y^2)$
$=-19xy+y^2$
2A-3B-C
\(=2\left(4x^2-5xy+3y^2\right)-3\left(3x^2+2xy+y^2\right)+x^2-3xy-2y^2\)
\(=8x^2-10xy+6y^2-9x^2-6xy-3y^2+x^2-3xy-2y^2\)
\(=-19xy+y^2\)
\(a,x^3\left(3x^2-x-\dfrac{1}{2}\right)\)
\(=3x^5-x^4-\dfrac{1}{2}x^3\)
\(b,\left(5xy-x^2+y\right).\dfrac{2}{5xy^2}\)
\(=\dfrac{2}{y}-\dfrac{2x}{5y^2}+\dfrac{2}{xy}\)
\(c,\left(4x^3-3xy^2+2xy\right)\left(-\dfrac{1}{3}x^2y\right)\)
\(=-\dfrac{4x^5y}{3}+x^3y^3-\dfrac{2x^3y^2}{3}\)
\(-5xy\left(4x^2-3xy+2\right)\)
\(=-5xy\cdot4x^2+5xy\cdot3xy-5xy\cdot2\)
\(=-20x^3y+15x^2y^2-10xy\)
`-5xy . (4x^2 - 3xy + 2) `
`= -5xy . 4x^2 + 5xy . 3xy - 5xy . 2`
`= -20x^3 y + 13x^2 y^2 - 10xy `